PELATIHAN HANDS ON PEMERIKSAAN MIKROSKOPIS MYCOBACTERIUM TUBERCULOSIS BAGI AHLI TEKNOLOGI LABORATORIUM MEDIS (ATLM) DI KOTA JAMBI - Maria Estela Karolina; Fairuz Fairuz; Patrick William Gading; Ade Susanti; Suhair Suhair (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2023)
ABSTRACTTuberculosis (TB) is a disease that attacks the respiratory system and is an infectious disease. TB is caused by rod-shaped bacteria, obligate aerobes, namely Mycobacterium tuberculosis which can also attack other parts of the body such as the brain and bones. Tuberculosis can be transmitted through droplets from sufferers when talking, coughing, sneezing. Microscopic examination is the key in carrying out TB control and prevention programs in establishing a diagnosis and evaluating treatment for TB sufferers. For this reason, refreshment training for Medical Laboratory Technologists (ATLM) in Jambi City needs to be carried out, to increase knowledge and skills in microscopic diagnosis of pulmonary TB. This activity will be held on September 30 2023 with 42 ATLM participants in the biomedical laboratory of the Faculty of Medicine and Science Jambi University. Activities include lectures, practice in the form of seminars and training.The results of the pretest and posttest evaluation showed an increase in ATLM understanding. It is recommended that the Jambi City Health Service continue to provide training for ATLM such as microscopic, culture and molecular TB in order to make Indonesia TB free by 2030.Keywords: Medical Laboratory Technologist (ATLM), Tuberculosis, Mycobacterium tuberculosis, Microscopic examination ABSTRAKTuberkulosis (TB) adalah penyakit yang menyerang sistem pernapasan dan termasuk dalam penyakit menular. TB disebabkan oleh bakteri berbentuk batang, aerob obligat yaitu Mycobacterium tuberculosis yang dapat juga menyerang bagian tubuh yang lain seperti otak, tulang. Penyakit tuberculosis dapat ditularkan melalui droplet dari penderita saat bicara, batuk, bersin. pemeriksaan mikroskopis merupakan kunci dalam menjalankan program pengendalian dan pencegahan TB dalam menegakkan diagnosis dan evaluasi pengobatan penderita TB. Untuk itu pelatihan refreshment bagi Ahli Teknologi Laboratorium Medik (ATLM) di kota jambi perlu dilakukan, untuk meningkatkan pengetahuan dan keahlian dalam diagnosis mikroskopis TB paru.Kegiatan ini dilaksanakan pada tanggal 30 September 2023 dengan jumlah peserta 42 orang ATLM di laboratorium biomedik fakultas kedokteran dan ilmu Kesehatan Universitas Jambi. Adapun bentuk kegiatannya berupa ceramah, praktek dalam bentuk seminar dan pelatihan. Hasil evaluasi pretest dan postest adanya peningkatan pemahaman ATLM. Disarankan untuk Dinas Kesehatan Kota Jambi untuk terus memberikan pelatihan bagi ATLM mikroskopis, kultur, molekuler TB guna mewujudkan Indonesia bebas TB tahun 2030.Kata kunci: Ahli Teknologi Laboratorium Medik (ATLM), Tuberkulosis, Mycobacterium tuberculosis, Pemeriksaan mikroskopis